Pemertahanan bahasa Indonesia sebagai bahasa warisan pada keluarga diaspora di Swiss: Motivasi, strategi, dan tantangan - Pratama, Fendy Yogha; Putri, Ardhana Reswari Diyah (Universitas Mulawarman, 2026)
This study aims to explore the motivations, strategies, and challenges faced by Indonesian diaspora families in Switzerland in maintaining Indonesian as a heritage language. Using a case study approach, this research delves into the real-life perceptions and experiences of the participants. Nine participants, selected through purposive sampling, were interviewed in depth. The data obtained were then analyzed using thematic analysis to map emerging patterns of motivations, strategies, and challenges. The findings reveal that parents’ primary motivations are driven by the need for communication with extended family in Indonesia, a strong sense of cultural identity, and practical benefits for the future. Strategies employed include self-directed teaching, consistent use of Indonesian at home, and participation in BIPA (Indonesian for Foreign Speakers) courses. Nevertheless, these efforts encounter challenges such as children’s reluctance to use the language, the dominance of the majority language, and differing perspectives within the extended family. These findings underscore that the success of heritage language maintenance requires multilayered support from families, schools, and the broader community.